The Topical Effect of Binahong Fraction Leaves [Anredera Cordifolia (Ten.) Steenis] on Increased Epithelization and Hydroxyproline Level at Incision Wound in Rats - Meriyanti P.S.; M.T. Kamaluddin; Theodorus (Biomedical Journal of Indonesia, 2020)
Binahong leaves [Anredera cordifolia (Ten.) Steenis] are easily found in Indonesia, efficacious and had been used as a wound-healing herbal medicine. This research aimed to assess the effectiveness of acetate ethyl fraction in binahong leaves [Anredera cordifolia (Ten.) Steenis] as a topical agent to the histopathology changes including increased epithelization and histochemistry examination by assessing hydroxyproline level in the acute incision wound healing process in Sprague Dawley rats. An in vivo laboratory experiment, using the Pre and Post Test Only Control Group Design. The subject was Sprague Dawley white male rats, randomly divided into 5 (five) treatment groups, a negative control group (gel-based), positive control group (Bioplacenton), 1% concentration of acetate ethyl fraction from binahong leaves group (FADB 1%), 2% concentration of acetate ethyl fraction from binahong leaves (FADB 2%) and 4% concentration of acetate ethyl fraction from binahong leaves (FADB 4%). The collected data was analyzed using SPSS programme version 21.0 with homogeneity test, normality test, Wilcoxon test, Mann Whitney test, Independent T-test, and Post Hoc confirmation using LSD test. In 4th-day skin tissue examination, the effectiveness of 4% concentration of acetate ethyl fraction from binahong leaves was not significantly different from Bioplacenton effectiveness in increasing epithelization and hydroxyproline level in the 10th-day skin tissue examination.